The Kritik Islam Terhadap Konsep Etika Barat - Isna Arliana Goncing; Indo Santalia (Mazalat: Jurnal Pemikiran Islam, 2026)
This article discusses Western ethics from a critical and Islamic perspective. Western ethics is often based on secularism and rationalism, which is considered to neglect the spiritual and metaphysical aspects of human beings. This research is a library research, as it relies on written data that discusses the topic being examined by the author. Each piece of literature obtained by the researcher presents data that is processed using deductive, inductive, and comparative techniques. From an Islamic perspective, Western ethics has several weaknesses, such as a lack of awareness of God's presence and individual accountability to Him. This article also discusses the concept of Islamic ethics, which emphasizes the importance of awareness of God's presence, individual responsibility, and balance between rights and obligations. By understanding the Islamic critique and perspective on Western ethics, we can gain a broader insight into morality and ethics in a global context.